Low-background gamma-ray spectrometry for the international monitoring system. (August 2017) - Greenwood, L.R.; Cantaloub, M.G.; Burnett, J.L.; Myers, A.W.; Overman, C.T.; Forrester, J.B.; Glasgow, B.G.; Miley, H.S.
Abstract: PNNL has developed two low-background gamma-ray spectrometers in a new shallow underground laboratory, thereby significantly improving its ability to detect low levels of gamma-ray emitting fission or activation products in airborne particulate in samples from the IMS (International Monitoring System). The combination of cosmic veto panels, dry nitrogen gas to reduce radon and low background shielding results in a reduction of the background count rate by about a factor of 100 compared to detectors operating above ground at our laboratory. Highlights: Two new low-background gamma detectors in shallow underground laboratory at PNNL The detectors are designed for use with the International Monitoring System Gamma-ray background about a factor of 100 lower than our surface gamma detectors Detection limits are about a factor of 10 lower than surface gamma detectors